Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Intraspecific haplotype diversity in Cherleria sedoides L. (Caryophyllaceae) is best explained by chloroplast capture from an extinct species - Abigail J. Moore; Francisco J. Valtueña; Markus S. Dillenberger; Joachim W. Kadereit; Chris D. Preston (Alpine Botany, 2017)

GB Non-native Species Information Portal: documenting the arrival of non-native species in Britain - Helen E. Roy; Chris D. Preston; Colin A. Harrower; Stephanie L. Rorke; David Noble; Jack Sewell; Kevin Walker; John Marchant; Becky Seeley; John Bishop; Alison Jukes; Andy Musgrove; et al. (Biological Invasions, 2014)

Horizon scanning for invasive alien species with the potential to threaten biodiversity in Great Britain - Helen E. Roy; Jodey Peyton; David C. Aldridge; Tristan Bantock; Tim M. Blackburn; Robert Britton; Paul Clark; Elizabeth Cook; Katharina Dehnen‐Schmutz; Trevor Dines; Michael Dobson; François Edwards; et al. (Global Change Biology, 2014)
Invasive alien species ( IAS ) are considered one of the greatest threats to biodiversity, particularly through their interactions with other drivers of change. Horizon scanning, the systematic examination of future potential threats and opportunities, leading to prioritization of IAS threats is seen as an essential component of IAS management. Our aim was to consider IAS that were likely to impact on native biodiversity but were not yet established in the wild in Great Britain. To achieve this, we developed an approach which coupled consensus methods (which have previously been used for collaboratively identifying priorities in other contexts) with rapid risk assessment. The process involved two distinct phases: Preliminary consultation with experts within five groups (plants, terrestrial invertebrates, freshwater invertebrates, vertebrates and marine species) to derive ranked lists of potential IAS. Consensus‐building across expert groups to compile and rank the entire list of potential IAS. Five hundred and ninety‐one species not native to Great Britain were considered. Ninety‐three of these species were agreed to constitute at least a medium risk (based on score and consensus) with respect to them arriving, establishing and posing a threat to native biodiversity. The quagga mussel, Dreissena rostriformis bugensis , received maximum scores for risk of arrival, establishment and impact; following discussions the unanimous consensus was to rank it in the top position. A further 29 species were considered to constitute a high risk and were grouped according to their ranked risk. The remaining 63 species were considered as medium risk, and included in an unranked long list. The information collated through this novel extension of the consensus method for horizon scanning provides evidence for underpinning and prioritizing management both for the species and, perhaps more importantly, their pathways of arrival. Although our study focused on Great Britain, we suggest that the methods adopted are applicable globally.

Phylogeography of a Tertiary relict plant, Meconopsis cambrica (Papaveraceae), implies the existence of northern refugia for a temperate herb - FRANCISCO J. VALTUEÑA; CHRIS D. PRESTON; JOACHIM W. KADEREIT (Molecular Ecology, 2012)
The perennial herb Meconopsis cambrica , a western European endemic, is the only European species of the otherwise Himalayan genus Meconopsis and has been interpreted as a Tertiary relict species. Using rbc L and ITS sequence variation, we date the split between M. cambrica and its sister clade Papaver s.str. to the Middle to Upper Miocene (12.8 Myr, 6.4–19.2 Myr HPD). Within M. cambrica , cpDNA sequence variation reveals the existence of two groups of populations with a comparable level of genetic variation: a northern group from Great Britain, the Massif Central, the western Pyrenees and the Iberian System, and a southern group from the central and eastern Pyrenees. Populations from the Cantabrian Mountains were placed in both groups. Based on ITS sequence variation, the divergence between these two groups can be dated to 1.5 Myr (0.4–2.8 Myr HPD), and the age of the British populations is estimated as 0.37 Myr (0.0–0.9 Myr HPD). Amplified fragment length polymorphism results confirm the distinctive nature of the populations from Britain, the Massif Central and the central and eastern Pyrenees. These patterns of latitudinal variation of M. cambrica differ from patterns of longitudinal differentiation found in many other temperate species and imply glacial survival of the northern populations in northerly refugia. The primary differentiation into northern and southern cpDNA groups dates to near the onset of the Quaternary and suggests that an ancient phylogeographic pattern has survived through several glacial periods. Our data provide evidence that the species has persisted for a long period with a highly fragmented and probably very localized distribution.

Atmospheric nitrogen deposition explains patterns of plant species loss - COLIN J. McCLEAN; LEON J. L. van den BERG; MIKE R. ASHMORE; CHRIS D. PRESTON (Global Change Biology, 2011)
Atmospheric nitrogen ( N ) deposition across Europe increased substantially from the 1950s to the 1990s. Targeted surveys suggest a negative correlation between N deposition and species richness within quadrats in sensitive habitats. However, it remains unclear whether plant species losses at national recording scales are correlated with nitrogen deposition. We relate plant species losses before 1987 in Great Britain to reduced and oxidized N deposition, land use change and climate change. The mean Ellenberg fertility ( N ) indices of plant species lost in each 100 km 2 cell before 1987 was compared with those of species that were recorded between 1987 and 1999. In 45% of squares, indices of species lost were significantly lower than those for species present after 1986. For 17%, primarily upland, squares, the opposite effect was found. A generalized least squares regression model, with difference in the mean Ellenberg N index between samples as the dependent variable, showed that higher deposition of reduced N was significantly associated with selective loss of species with a lower index. Arable land use and change in arable land use also demonstrated this positive relationship. Rough grazing, change in rough grazing, change in pasture and change in annual precipitation showed negative effects. Difference in Ellenberg R index was highly correlated with difference in Ellenberg N and was negatively correlated with oxidized N deposition, suggesting that the lack of a significant effect of oxidized N deposition on Ellenberg N was because it had effects through both acidification and eutrophication, while the effect of reduced N deposition was primarily through eutrophication. Our results suggest that N deposition, along with land use and precipitation changes, has been a significant driver of local plant extinctions. With N deposition increasing in many parts of the world, local extinctions of plant species may be experienced in other regions.